2013
DOI: 10.1038/nchem.1830
|View full text |Cite
|
Sign up to set email alerts
|

Validation of N-myristoyltransferase as an antimalarial drug target using an integrated chemical biology approach

Abstract: Malaria is an infectious disease caused by parasites of the genus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
336
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 201 publications
(356 citation statements)
references
References 52 publications
9
336
0
1
Order By: Relevance
“…Because binding of the peptides does not affect acyl-CoA binding to the N-terminal motif ( 33,53,54 ), compounds that can recognize the C-terminal binding domain of the NMT proteins of invading pathogens seem to be good candidates to specifi cally disrupt myristoylation without impacting acylation of the proteins of the host (28)(29)(30)(31)(32)(34)(35)(36). As examples, the development of Plasmodium falciparum in erythroid cells is blocked by several chemicals inhibiting the P. falciparum NMT enzyme (35)(36)(37)55 ). The inhibition of myristoylation of the HIV Gag protein prevents its membrane association and blocks viral budding ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because binding of the peptides does not affect acyl-CoA binding to the N-terminal motif ( 33,53,54 ), compounds that can recognize the C-terminal binding domain of the NMT proteins of invading pathogens seem to be good candidates to specifi cally disrupt myristoylation without impacting acylation of the proteins of the host (28)(29)(30)(31)(32)(34)(35)(36). As examples, the development of Plasmodium falciparum in erythroid cells is blocked by several chemicals inhibiting the P. falciparum NMT enzyme (35)(36)(37)55 ). The inhibition of myristoylation of the HIV Gag protein prevents its membrane association and blocks viral budding ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although amide linkage of the myristate to the glycine residue appears irreversible, a structural conformational property of some acyl-proteins, called the myristoylswitch, can remove the aliphatic tail from the lipid bilayer and dissociate the proteins from their membrane-bound location ( 25,27 ). The acyl-transferase activity of the NMT enzymes is specifi c toward myristoyl-CoA (C 14 -CoA) and is essential for the intracellular development of pathogens (28)(29)(30)(31)(32)(33)(34)(35)(36). Chemicals inhibiting myristoylation of proteins are potent drugs against parasitic protozoa and fungi.…”
Section: Affi Nity Purifi Cation Msmentioning
confidence: 99%
“…Functionalized lipidation probes have been used to prove the exploitation of host-cell-mediated prenylation for membrane targeting of Legionella effectors (Ivanov et al 2010). Probes for a number of additional lipid modifications have been published and used to study a variety of diseases such as malaria and cancer (Thinon et al 2014;Wright et al 2014;Tate et al 2015). These could be useful to determine if T4SS effectors exploit other lipid modifications as membrane anchors.…”
Section: Functionalized Substrate Analogues To Profile Ptmsmentioning
confidence: 99%
“…Based on ligand similarity beyond the sulfonamide functionality we decided to investigate N-myristoyltransferase. Further, it has recently been validated as a novel antimalarian drug target in Plasmodium vivax by Wright et al 21 In this work it was shown on a structural basis that aromatic sulfonamides are capable of inhibiting N-myristoyltransferase, and hence we chose the published co-crystal structure of enzymes and sulfonamide inhibitors as the basis for our in silico analysis (PDB 2YND). Induced fit docking of our series of sulfonamides to P. vivax N-myristoyltransferase yielded consistent binding modes, in contrast to static docking runs that often led to severely distorted ligand conformations.…”
Section: In Silico Mode-of-action Analysismentioning
confidence: 99%